Kajian Potensi Pengunjung dalam Rangka Pengembangan Bisnis Wisata Alam (Studi Kasus Wisata Alam Kumkum di Kota Palangka Raya): Study of Visitor Potential in the Context of Nature Tourism Business Development (Case Study of Kumkum Nature Tourism in Palangka Raya City) - Shofiyah, Shofiyah (​Institute for Research and Community Services Universitas Muhammadiyah Palangkaraya, 2009)
Study of Visitor Potential in the Context of Nature Tourism Business Development (Case Study of Kumkum Nature Tourism in Palangka Raya City)